PRODUCTION PLANNING AND CONTROL SYSTEM WITH JUST IN TIME AND LEAN PRODUCTION : A REVIEW - Afriansyah Afriansyah; Amrifan Saladin Mohruni (Universitas Sriwijaya, 2019)
Manufacturing can be defined as applying physical and/or chemical processes to modify the structure, properties and/or appearance of a given starting material to produce parts or products. Manufacturing often entails combining multiple parts for the creation of assembled products. This study aimed to establish a general understanding of development production planning and control and typical production such as just in time and lean production. Method of this study through literature review. This study described activities related to production planning and production control, the difference between lean production and traditional production (push system), and the structure of lean production as known as Toyota system manufacturing.